Participatory forest management: A case of equity in the forest plantation establishment and livelihood improvement Scheme in Gathiuru and Hombe forests in Central Kenya. (International Journal of Scientific Research and Management (IJSRM), 2017)
The study analysis equity in participatory plantation establishment and livelihood scheme (PELIS) formally known as shamba (farm) system in Gathiuru and Hombe forests Kenya. This is done by determining annual inputs and outputs of three partners in PELIS including the Kenya forest service (KFS), three saw milling companies and the communities farming in Hombe and Gathiuru forests. The study uses Adams equity theory and applies the equity theory ratios as the basis of formulating equity under PELIS arrangements. The analysis is limited to a three year period (2012 to 2014), which corresponds to the number of years farmers cultivate in one plot under the scheme. Equity ratio analysis based on annual average annual output: input ratios for KFS 2012-2014 were 4.1:1; 2.6:1; and 3.1:1; for the three timber companies were 2.8:1; 3.1:1 and 1.9:1 while for community were 2.8:1; 2.4:1 and 2.8:1. The three year average ratios were 3.2:1 for KFS, 3.0:1 for the timber companies and 2.7:1 for communities. This indicates that the equity ratios were very close meaning that they all benefitted at the same level of respective inputs between 2012 and 2014. The study therefore concludes that applying the equity theory ratios can provide an opportunity to address inequity in PELIS under participatory forest management